2001
DOI: 10.1002/chir.10033
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separation of drugs and herbicides on a β‐cyclodextrin‐bonded stationary phase

Abstract: A chemically bonded beta-cyclodextrin chiral stationary phase for HPLC was prepared in a "one pot" process by the reaction of a phenylated beta-cyclodextrin with silica gel. Various racemic analytes such as drugs (aminoalcohol adrenergic beta-blockers, benzodiazepine anxiolytics, arylpropionic acid antiinflammatory agents) and herbicides (aryloxypropionic acids and esters) were separated on the prepared material. The column showed good chiral recognition ability for most of the solutes tested when using heptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
3
18
1
Order By: Relevance
“…Roussis et al 9 found β-caryophyllene to be the main constituent, but this substance was not found at all by Tazerouti et al 15 or Zafra et al 10 Mirov et al 25 reported α-pinene as the main compound, together with myrcene, in agreement with our findings. Tazerouti et al 15 also found myrcene to be the principal constituent.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Roussis et al 9 found β-caryophyllene to be the main constituent, but this substance was not found at all by Tazerouti et al 15 or Zafra et al 10 Mirov et al 25 reported α-pinene as the main compound, together with myrcene, in agreement with our findings. Tazerouti et al 15 also found myrcene to be the principal constituent.…”
Section: Resultssupporting
confidence: 92%
“…Roussis et al 9 found β-caryophyllene to be the main constituent, but this substance was not found at all by Tazerouti et al 15 or Zafra et al 10 Mirov et al 25 reported α-pinene as the main compound, together with myrcene, in agreement with our findings. Tazerouti et al 15 also found myrcene to be the principal constituent. Zafra et al 10 reported as main constituents sabinene followed by α-pinene for during all the months of the investigation; also, in the essential oil of the twigs, sabinene was the major compound, followed by α-pinene and terpinolene.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Some of the solutes were racemic mixtures whereas in others one enantiomer was predominant (see structures in Table 1). The enantiomeric purity of the solutes studied had been checked in previous works by polarimetric detection [8,13].…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The mechanism of chiral recognition implies a synergistic interaction of carboxylic acid analyte with the chiral selector and achiral free -aminopropyl units on silica. (Vinkovic et al, 2001) In a study by Badjah-Hadj-Ahmed (Tazerouti et al, 2002), eleven 2-aryloxypropionic acids and esters herbicides were partially separated on the prepared phenylated -CD CSP when using heptane and either IPA or chloroform as organic mobile phase modifier.…”
Section: Enantioseparation and Enantioselective Analysis Of Chiral Hementioning
confidence: 99%